2023
DOI: 10.3390/wevj14060154
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effective Factors on Vehicles Integrated Photovoltaic (VIPV) Performance: A Review

Abstract: Integrating photovoltaic technology has undergone significant development in recent years, owing to its manifold advantages. One of the most recent domains where this technology has found application is within the transportation sector. The utilization of this technology possesses the potential to initiate a new revolution in transportation by enhancing the range and reducing fuel consumption in vehicles. The performance of these systems is influenced by numerous factors, which have been thoroughly examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…A few more articles reviewed the current progress on fuel cell vehicles [12], comparisons of optimal sizing and power management for hybrid fuel cell vehicles (fuel cell/battery/supercapacitors) [13], and proton exchange membrane-based fuel cell application for road transport [14]. The reviews on recent trends in incorporating photovoltaics into boats [15], passenger vehicles [16] and effective factors on the performance of vehicle integrated photovoltaics to run on solar energy are published in the literature [17]. So, there are many articles in the literature that review single-technology vehicles, i.e., either on biofuel-based vehicles or electric vehicles or fuel cell vehicles or solar vehicles.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…A few more articles reviewed the current progress on fuel cell vehicles [12], comparisons of optimal sizing and power management for hybrid fuel cell vehicles (fuel cell/battery/supercapacitors) [13], and proton exchange membrane-based fuel cell application for road transport [14]. The reviews on recent trends in incorporating photovoltaics into boats [15], passenger vehicles [16] and effective factors on the performance of vehicle integrated photovoltaics to run on solar energy are published in the literature [17]. So, there are many articles in the literature that review single-technology vehicles, i.e., either on biofuel-based vehicles or electric vehicles or fuel cell vehicles or solar vehicles.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…Flexible photovoltaic (PV) technologies have gained considerable attention for new energy-generating applications, such as buildingintegrated PVs [1][2][3][4][5][6], vehicle-integrated PVs [7][8][9], and product-integrated PVs [2,10,11]. Flexible thin-film solar cells [12] are lightweight, allowing high specific power (kW/kg) and mechanical robustness, which are of particular interest, and a lower production cost by employing large-scale production, enabling high throughput (e.g., roll-to-roll manufacturing).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have discussed the feasibility of PV-fed transportation and revealed its potential [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The limitations of the car body's geometrical area and the energy requirements have induced solar cell researchers to develop more innovative solar cells [29,30]. Specifically, various generations of solar cells were considered for application to vehicles.…”
Section: Introductionmentioning
confidence: 99%